Comparative Analysis of Mast Cell Density in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma - Nandita K.P; Srikant N; Karen Boaz; Amitha J Lewis; Nidhi Manaktala (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Oral squamous cell carcinoma (OSCC) is one of the most common malignancies of the oral cavity. One of the foremost cells recruited near the tumor front is the mast cells. Mast cells produce angiogenic mediators such as fibroblast growth factor (FGF), transforming growth factor (TGF), tumor necrosis factor, (TNF), and the vascular endothelial growth factor (VEGF) 1. which are increased in precancerous lesions and found in more abundance in OSCC.Accumulation of mast cells around the tumor margins and their release of potent pro-angiogenic and angiogenic factors may represent a tumor-host interaction which probably favors tumor progression. The progression of oral lesions from dysplasia to oral squamous cell carcinoma is characterized by an “angiogenic switch” that is associated with an increase in the neovascularization of the subepithelial lamina propria, which may be considered an indicator of malignant transformation. 2MCs also represent a rich source of proteases, especially ofmast cell tryptase and chymase, which directly degrade the extracellularmatrix through their proteolytic activity and thus indirectly stimulate angiogenesis and facilitate invasion and metastasis. Theliterature has proven that mast cells can be an indicator of increased angiogenesis and hence can help in the prediction of carcinogenesis, its progression, and also the prognosis of the malignant lesions.Aim of the Study: To compare the number, morphology, and distribution of mast cells in different grades of oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC) and to study their role in tumor growth and pathogenesisMaterials and Methods: A total of 39 cases, which included 13 cases of dysplasia and 26 of OSCC were included in the study. Tissue sections were stained with H&E and 1% toluidine blue was used to evaluate mast cells. Mast cells were counted manually using an ocular grid throughout the tissue sections in 10 representative grid fields in a stepladder fashion. (40x magnification).The mean mast cell density (MCD) of 10 fields was calculated and was expressed as mean (standard deviation) per mm3,4. Mast cells were then categorized as typical, atypical, or granular mast cells and statistically analyzed.5Result: In the present study, there is a decrease in the number of mast cells with severe grades of dysplasia and poorer grades of oral squamous cell carcinoma. ConclusionMast cells may induce the tumor progression by providing a mitogenic stimulation or angiogenesis-the hallmark of the tumor growth and metastasis through the release of various mediators.